Kesetaraan Gender Dalam Hukum Ketenagakerjaan - Anik Iftitah; Nanda Romei Puspitasari; Niken Yulianti; Mukhammad Taufan Perdana Putra; Kunarso Kunarso (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
In 2019, Indonesia faced several issues related to gender equality in labor law. The latest data from the Central Statistics Agency (BPS) shows that the wage gap between men and women in Indonesia continues. in 2020 women in Indonesia earn a salary of 84.4% of the amount of salary received by men. This research attempts to analyze women's employment law in Indonesia. In this case an analysis of cases of violations of labor rights against women and how they are protected according to the Labor Law. From the enactment of this law in Indonesia, especially before the Amendment to the 1945 Constitution and the promulgation of Law no. 10 of 2004, and its amendment Number 12 of 2011 concerning the types and levels of statutory regulations Article 7 of the Law regulates as follows: the 1945 Constitution of the Republic of Indonesia, TAP MPR, Laws/Perpu, Government Regulations, Presidential Regulations and regional laws and regulations. The stage of ratification of the announcement, dissemination and announcement of the Secretary of State. The purpose of this research is to analyze the level of gender equality, the challenges of achieving equality in Indonesia and the field of employment. The results of this research show that gender inequality persists in Indonesia, but inequality has decreased over time, meaning that opportunities for men and women have become more equal. However, there is still room for improvement in gender equality. There are also several institutional and socio-cultural obstacles, such as the lack of agreement between women workers and employers fighting for gender equality in the workplace, gender equality regulations are still not optimally implemented and workers' awareness of human rights is still low. them, and the low bargaining position of women workers. For this reason, the government needs to improve gender equality by strengthening law enforcement on gender equality in the field of employment to increase cooperation between the central and regional governments to support the employment system. The type of research we use is normative legal research.